Effects of short‐term storage on sperm function in fish semen: a review - Pablo Contreras; Kelly Dumorné; Patricio Ulloa‐Rodríguez; Osvaldo Merino; Elías Figueroa; Jorge G. Farías; Iván Valdebenito; Jennie Risopatrón (Reviews in Aquaculture, 2020)
Storage of refrigerated semen is a simple and inexpensive procedure that can facilitate the management and reproduction programmes in aquaculture and allows to store semen for in vitro reproduction, quality analyses, hatchery production support, selective in vitro breeding, disease diagnosis, transportation, cryopreservation and advanced molecular studies. Implementation of semen short‐term storage protocols for threatened or endangered fish represents a useful strategy for preservation of these species. Semen cold storage as technique is a useful strategy for the conservation of fish sperm. Analysing the male broodstock sperm quality during cold storage is a tool to identify the reproductive ability of cultivated fish. Thus, in this review we analysed the most relevant factors that affect sperm quality during cold storage of male broodstock semen as well as its effects on motility, viability, mitochondrial membrane potential, superoxide anion level and DNA fragmentation.